Spotlight on Britain - Sheerin, Susan (Oxford University Press, 1990)
This book gives a region-by-region account of life in the United Kingdom. The wide variety of topics includes London, TV and Radio, Liverpool and the Beatles, Stratford and Shakespeare, Northern Ireland. Interesting information combines with opportunities for lively discussion, and students are provided with comprehension questions and language practice exercises.